Religious Identity and National Heritage Empirical-Theological Perspectives. - Anthony, Francis-Vincent. (Leiden : BRILL, 2012)
What is the interplay between religion and national culture in modern times? Distinguished scholars reflect on this question based on empirical research. They offer a vast set of insights about how religious identity is connected to the national heritage in which people are born and brought up.
Two Alienation Scenarios: Explaining the Distance between Catholics and Roman Catholic Church in the NetherlandsPART THREE: SECULAR-MODERN PERSPECTIVE; Values Heritage and Diffused Religion; Confirmation Work in Europe Religious Identity, National Heritage, and Civil Society: Insights from an International Empirical and Comparative Study in Seven Countries; Teachers' Attitudes on Religion in Modernity and its Impact on Belief; Atheism and Secularism: Cultural Heritage in East Germany; Secularization as National Heritage? Empirical Research on Religious Education in Eastern Germany; Index
Description based upon print version of record.
Includes bibliographical references and index.
Keywords: Identification (Religion) -- Congresses; Identification (Religion).; Nationalism -- Religious aspects -- Congresses; Nationalism -- Religious aspects; Identification (Religion) -- Congresses; Nationalism -- Religious aspects -- Congresses; RELIGION / Sexuality & Gender Studies; Electronic books